Agências reguladoras como poder concedente em contratos de concessão - Gabriel Ribeiro Fajardo (2023)
Regulatory agencies were authorized in the Brazilian administrative organization from the 1990s onwards. Conceived to bring technicality and legal certainty to private investment, in a context of privatizations and concessions of public services, the agencies were created based on specific laws, without there was a legal regime that unified its role in the national public administration. In the delegated services, these agencies would be essential for creating a safe environment for large investments, since they would be isolated from political pressure and electoral cycles. They would be responsible for regular services and contracts that have as their hallmark the long term, risk, mutation and the various interests entangled in complex projects. These entities, however, also took on the role of granting power in the concession contracts. This new configuration brought regulatory agencies the challenge of maintaining neutrality in the public-private relationship and, at the same time, adopting decisions that are specific to the holder of the service granted. This research aims, therefore, to analyze the reasons and foundations for the undertaking of regulatory agencies in Brazilian law, as well as to investigate how concession contracts pose challenges to regulation due to their own characteristics, in order to, in the end, debate whether such agencies should assumes granting power functions in these configurations.